Kidney stone disease and osteoporosis - topic issues of comorbidity - Ilia Kordubailo; Oleg Nikitin; Olga Nishkumay; Pavlo Samchuk (Bogomolets National Medical University, 2021)
the prevalence of kidney stone disease (KSD) and osteoporosis (OP) increases every year. In the prevention of osteoporosis, it is important to consume a sufficient amount of calcium-rich foods in the daily diet, as well as the use of calcium. One of the important reasons for the insufficient use of calcium-containing products and medicines is the anxiety not only of patients, but, very importantly, of doctors as much as possible. This has serious justification, as nephrolithiasis occurs in approximately 5% of the population, and the risk of developing kidney stones during life is 8-10%. It is believed that secondary hyperparathyroidism, which is caused by hypocalcemia due to insufficient consumption of calcium-containing products and impaired renal function, leads to increased bone resorption, formation of kidney stone disease. It is important to consider that against the background of hypertensive, atherosclerotic kidney disease, tubulo-interstitial lesions of the kidneys with decreasing glomerular filtration rate decreases the synthesis of 1α-hydroxylase - an enzyme by which 25-hydroxycholecalciferol (25 (OH) active D3, calcium) form of vitamin D3-1.25 dihydroxycholecalciferol (1.25 (OH) 2D3, calcitriol - D-hormone) and secondary hyperparathyroidism develops. In this case, the purpose of correction along with the treatment of urolithiasis (spa treatment, given the attendance of the presence of KSD, to carry out the distance lithotripsy), intake of active metabolites of vitamin D (should be started with low doses, independent of the initial PTH concentration, and then titrated based on the PTH response) conducting X-ray densitometry.